On Lightweight Intrusion Detection: Modeling and Detecting Intrusions Dedicated to OLSR Protocol - Mouhannad Alattar; Françoise Sailhan; Julien Bourgeois (International Journal of Distributed Sensor Networks)
Mobile ad hoc networks mostly operate over open, adverse, or even hostile environments and are, therefore, vulnerable to a large body of threats. Conventional ways of securing network relying on, for example, firewall and encryption, should henceforth be coupled with advanced intrusion detection. To meet this requirement, we first identify the attacks that threaten ad hoc networks, focusing on the Optimized Link State Routing Protocol. We then introduce IDAR, a signature-based Intrusion Detector dedicated to ad hoc routing protocols. Contrary to existing systems that monitor the packets going through the host, our system analyses the logs so as to identify patterns of misuse. This detector scopes with the resource-constraints of ad hoc devices by providing distributed detection; in particular, depending on the level of suspicion and gravity, in-depth cooperative diagnostic may be launched. Simulation-based evaluation shows limited resource consumption (e.g., memory and bandwidth) and high detection rate along with reduced false positives.